PERANCANGAN SISTEM ABSENSI BERBASIS WEB MENGGUNAKAN QR CODE DI SMP FATAHILLAH - Alessandro Delpiero; Abdul Azis; Cahyadi (Journal of Research and Publication Innovation, 2026)
Conventional paper-based attendance systems often face challenges such as the risk of data corruption, attendance manipulation (such as leaving attendance on the desk), and a lengthy recapitulation process. This research aims to design and build a web-based student attendance system that integrates Quick Response (QR) Code technology to improve the efficiency and accuracy of attendance data. The system was developed using the PHP programming language with a MySQL framework and database. The system development method used is the Waterfall approach, encompassing the stages of needs analysis, design, coding, and testing. The system's working mechanism involves creating a unique QR Code for each student that can be scanned using the device's camera at school. The scanned data is automatically recorded in a database in real time, which can then be accessed by teachers or administrators in the form of periodic reports. Test results show that this QR Code-based attendance system can minimize data input errors and speed up the attendance recapitulation process by up to 80% compared to manual methods. The implementation of this system provides a practical solution for educational institutions to monitor student discipline more transparently, accurately, and effectively.